2019
DOI: 10.1186/s12966-019-0786-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a park refurbishment in a low socioeconomic area on physical activity: a cost-effectiveness study

Abstract: Background Physical inactivity is the fourth highest cause of death globally and is a major contributor to increases in healthcare expenditure. Improving public open spaces such as parks in areas of low socio-economic position (SEP) may increase recreational physical activity in disadvantaged populations. We assessed the cost-effectiveness of the installation of a play-space in a large metropolitan park in a low socioeconomic area based on changes in physical activity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Of the sample object of this study ( n = 31), 48.38% ( n = 15) of the papers established a direct relationship between the design, characteristics and equipment of the park with an increase in visits, a greater and more effective use of the park, and a greater intensity of PA, with 32.25% ( n = 10) being remodelled, innovative, contemporary and sustainable parks with special characteristics [ 4 , 53 , 62 , 64 , 69 , 72 , 75 , 77 , 80 ]. If the needs of users are also taken into account in the remodelling or design of new parks, 16.12% ( n = 5) of the studies analysed concluded that it can create a positive effect on the number of visitors and, therefore, an increase in PA performed [ 49 , 66 , 71 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the sample object of this study ( n = 31), 48.38% ( n = 15) of the papers established a direct relationship between the design, characteristics and equipment of the park with an increase in visits, a greater and more effective use of the park, and a greater intensity of PA, with 32.25% ( n = 10) being remodelled, innovative, contemporary and sustainable parks with special characteristics [ 4 , 53 , 62 , 64 , 69 , 72 , 75 , 77 , 80 ]. If the needs of users are also taken into account in the remodelling or design of new parks, 16.12% ( n = 5) of the studies analysed concluded that it can create a positive effect on the number of visitors and, therefore, an increase in PA performed [ 49 , 66 , 71 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Focusing efforts on the remodelling and/or design of parks in areas of low socioeconomic status is essential from the perspective of health and PA. This is because improving public spaces in disadvantaged areas can increase recreational PA [ 4 , 62 , 64 ]. This is not only beneficial for children from disadvantaged backgrounds, but it also applies to other contexts where, as current data indicate, park use is higher among boys than girls [ 49 , 64 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to sport, it is necessary to support and create the conditions for daily implementation of MVPA in all children and adolescents, regardless of the SES category. Improving public open spaces in low-SES areas by installing play spaces for recreational PA [77] or expanding school-related PA (including active recess, physical education lessons [78,79] and after-school nursery [80]) has an impact on increasing day-to-day PA [80] and reducing children's obesity [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that further research to identify how to sustainably increase park-based physical activity for different communities is worth pursuing. Moreover, studies have found park refurbishments a cost-effective way to increase physical activity [ 40 ]. Innovative amenities may be required.…”
Section: Discussionmentioning
confidence: 99%